Data driven evaluation of healthy volunteer characteristics at screening for phase I clinical trials to inform on study design and optimize screening processes. Issue 6 (11th August 2021) - Deiteren, Annemie; Coenen, Erwin; Lenders, Sabine; Verwilst, Peter; Mannaert, Erik; Rasschaert, Freya
Abstract: Protocols for clinical trials describe inclusion and exclusion criteria based on general and compound‐specific considerations to ensure subject safety and data quality. In phase I clinical trials, healthy volunteers (HVs) are screened against these criteria that often specify predefined eligibility ranges for vital signs, electrocardiogram, and laboratory tests. HVs are excluded if baseline parameters deviate from these ranges even though this may not indicate underlying pathology, which could delay trial execution. Data from 3365 HVs participating in 9670 screening visits for 94 phase I HV trials, conducted between December 2008 and May 2019 at the Janssen Clinical Pharmacology Unit, were retrospectively analyzed. Commonly predefined protocol ranges were overlaid with HV data to estimate predicted screen failure rates (SFRs). Of the overall population, 91% was White and 64% were men with mean age of 42.8 ± 12.5 years. High predicted SFRs are related to cardiovascular/metabolic (body mass index, heart rate [HR], blood pressure [BP], and corrected QT Fridericia's formula [QTcF]), renal (estimated glomerular filtration rate [eGFR]), liver (alanine aminotransferase [ALT], and total bilirubin), and coagulation (prothrombin time [PT]) parameters. Predicted SFRs increased with age for high systolic and diastolic BP, QTcF interval, and eGFR. In contrast, lower SFRs in the older age groups were seen for low diastolic BP, liver function test, ALT, PT, and total bilirubin. This analysis can be used to inform on study design, protocol inclusion and exclusion criteria, and to optimize the screening process. Data‐driven critical appraisal of proposed inclusion and exclusion criteria using a risk‐based approach may significantly reduce screen failure rates without compromising subjects' safety.